Disseminated infection with Nocardia otitidiscaviarum in a patient under steroid therapy. Issue 2 (7th January 2020) - Sah, Ranjit; Khadka, Shusila; Neupane, Samikshya; Nepal, Gaurav; Singla, Sonam; Kumari, Pankhuri; Sah, Sanjit; Sah, Ranjana; Sah, Shyam Sundar; Adhikari, Mahesh; Shah, Niranjan Prasad; Pokharel, Bharat Mani; et al.
Key Clinical Message: Corticosteroid recipients with lung infections should be suspected of having nocardiosis; however, nocardiosis can easily mimic malignancy, tuberculosis, or fungal infection. Though cultural identification is possible, it might be missed due to its slow growth pattern.. Therefore, if filamentous bacteria are seen during staining, plate incubation time should be extended. Abstract : Corticosteroid recipients with lung infections should be suspected of having nocardiosis; however, nocardiosis can easily mimic malignancy, tuberculosis, or fungal infection. Though cultural identification is possible, it might be missed due to its slow growth pattern.. Therefore, if filamentous bacteria are seen during staining, plate incubation time should be extended.